"There is also time to dance": art, identity, and politics.: Interview with Nina Pacari - Vargas Araujo, Edwar (2023)
The name of Nina Pacari refers to the political figure, the indigenous leader, the public woman who has held high public offices, was the first indigenous woman to be Chancellor of the Republic, has been a congresswoman, constitutional judge, academic, among many other things. However, in this interview, a more everyday side is explored, of her youth experiences, her beginnings in social organizations, her connection with art, culture, and indigenous identity, which lead her to become the leader she is today.